1997
DOI: 10.1007/pl00005749
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stimulus conditions on the performance of antisaccades in man

Abstract: We investigated the effect of different spatial and temporal parameters on the saccadic reaction times (SRTs) of the antisaccades and on the frequency and the SRTs of erratic prosaccades in five adult human subjects. The subjects were instructed to aim their saccades to the side opposite to where a visual go-stimulus occurred. Parameters under consideration were: the gap duration (between 0 and 600 ms, and an overlap paradigm); the stimulus size (sizes of 0.1 degrees, 0.2 degrees, and 0.4 degrees, using the ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
80
4
5

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 35 publications
(35 reference statements)
10
80
4
5
Order By: Relevance
“…It is tempting to assume that this may be due to potential overtraining with these locations. However, this cannot account for the fact that similar trends have been reported in other studies employing both non-human primates (Boch et al 1984) and humans (Fischer and Weber 1997;Kalesnykas and Hallett 1994; J. M. Dafoe, J. R. Broughton, I. T. Armstrong, and D. P. Munoz, unpublished data). The apparent bias toward certain stimulus locations could, therefore represent a neurological bias in the actual oculomotor system.…”
Section: Influence Of Stimulus Location On Saccade Behaviormentioning
confidence: 56%
See 2 more Smart Citations
“…It is tempting to assume that this may be due to potential overtraining with these locations. However, this cannot account for the fact that similar trends have been reported in other studies employing both non-human primates (Boch et al 1984) and humans (Fischer and Weber 1997;Kalesnykas and Hallett 1994; J. M. Dafoe, J. R. Broughton, I. T. Armstrong, and D. P. Munoz, unpublished data). The apparent bias toward certain stimulus locations could, therefore represent a neurological bias in the actual oculomotor system.…”
Section: Influence Of Stimulus Location On Saccade Behaviormentioning
confidence: 56%
“…Hemifield preferences in humans may also be influenced by societal/cultural effects. Previous human studies have reported biases in SRT and direction errors favoring the initiation of rightward saccades compared with leftward saccades (Fischer and Weber 1997;; J. M. Dafoe, J. R. Broughton, I. T. Armstrong, and D. P. Munoz, unpublished results) This bias may be due, in part, to differences associated with reading patterns (i.e., horizontal-left-to-right) (Abed 1991) and would explain the absence of this trend in animals. If the oculomotor system is indeed optimized for generating saccades to certain locations, this would explain, in part, why the monkeys had particular difficulties in performing antisaccades to certain locations.…”
Section: Influence Of Stimulus Location On Saccade Behaviormentioning
confidence: 87%
See 1 more Smart Citation
“…There are two published studies examining the effects of stimulus eccentricity on antisaccade latencies in human subjects. In a study by Fischer and Weber (1997), a decrease in antisaccade latencies was seen with increasing stimulus eccentricity (ranging from 1° to 12° stimulus eccentricity). Fischer and Weber also found that antisaccade error rate increased with increasing eccentricity (Fischer & Weber 1997).…”
mentioning
confidence: 95%
“…In a study by Fischer and Weber (1997), a decrease in antisaccade latencies was seen with increasing stimulus eccentricity (ranging from 1° to 12° stimulus eccentricity). Fischer and Weber also found that antisaccade error rate increased with increasing eccentricity (Fischer & Weber 1997). On the contrary, Dafoe et al (2007) did not find a significant effect of eccentricity on antisaccade latencies.…”
mentioning
confidence: 95%